Incidental upper tract urothelial carcinoma presenting as pyonephrosis - K Manjula; Geethanjali Nagaraj; Krishna Shetty; CSBR Prasad (Wolters Kluwer Medknow Publications, 2017)
Upper tract urothelial carcinomas (UTUCs) are uncommon and account for only 5%-10% of urothelial carcinomas. The most common symptom of UTUC is gross or microscopic hematuria (70%-80%). A 55-year-old woman admitted with the history of fever and pain in abdomen for the past 20 days. Her history was not significant. She underwent right nephroureterectomy with the provisional clinical diagnosis of pyonephrosis with nonfunctioning kidney. Histopathological examination of nephrectomy specimen showed features of high-grade urothelial carcinoma with renal parenchyma invasion (T3N0M0). Here, we present a rare case of incidental UTUC presenting as pyonephrosis.